2007
DOI: 10.1007/s10764-007-9200-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Nutritional Profiles of Free-Ranging Alouatta Caraya in Northern Argentina: Lipoproteins; Amino Acids; Vitamins A, D, and E; Carotenoids; and Minerals

Abstract: Quantifying circulating nutrient concentrations in sera of free-ranging subjects will help to establish a basis from which we can evaluate the nutritional status and needs of the captive population. We collected serum samples from 26 free-ranging black-and-gold howlers (Alouatta caraya) in San Cayetano forest in northern Argentina. We analyzed them for concentrations of lipoproteins; amino Int J Primatol (acids; vitamins A, D, and E; carotenoids; and minerals. There are a few significant differences between se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 20 publications
8
12
1
1
Order By: Relevance
“…In terms of length and weight, as expected based on previous studies (e.g., Schmidt et al 2007 ;Rovirosa-Hernández et al 2012 ), we found that males are larger and heavier than females in the three studied species. In relation to hematological parameters between sexes, we found signifi cantly lower values in hemoglobin, hematocrit, and 195 RBC count in females of the three species as compared to males.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In terms of length and weight, as expected based on previous studies (e.g., Schmidt et al 2007 ;Rovirosa-Hernández et al 2012 ), we found that males are larger and heavier than females in the three studied species. In relation to hematological parameters between sexes, we found signifi cantly lower values in hemoglobin, hematocrit, and 195 RBC count in females of the three species as compared to males.…”
Section: Discussionsupporting
confidence: 91%
“…In general, values of cholesterol and triglycerides in both species from Tabasco were similar to those previously reported for A. palliata mexicana in Veracruz, Mexico (Crissey et al 2003 ), and A. caraya in Argentina (Schmidt et al 2007 ). In contrast, the cholesterol values were higher in A. pigra males from Campeche in comparison to A. pigra and A. palliata from Tabasco.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations